A 3.4‐in. Flexible High‐Resolution Full‐Color Top‐Emitting AMOLED Display. Issue 1 (1st July 2013) - Chida, Akihiro; Hatano, Kaoru; Inoue, Tatsunori; Senda, Naoyuki; Sakuishi, Tatsuya; Ikeda, Hisao; Seo, Satoshi; Hirakata, Yoshiharu; Yasumoto, Shunpei Yamazaki Seiji; Sato, Masataka; Yasuda, Yuki; Okazaki, Shoji; et al.
Abstract In this paper, we report a 3.4‐inch flexible top‐emitting AMOLED display with remarkably high resolution using oxide TFTs. Our transfer technology has an advantage of fabricating high‐performance TFTs and a high‐resolution AMOLED Display on a flexible substrate.